‘Christ, the Head of the Church?’ : authority, leadership and organisational structure within the Nkhoma Synod of the Church of Central Africa Presbyterian - Zeze, Willie Samuel Dalitso (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 2012.